Etude numérique de l'amélioration de la portance des sols par différentes techniques - Chekima, Djihane; Chikha, Asma; Beya, Alia; Didi, Maroua (université d'eloued, 2023)
"The calculation of the bearing capacity of the foundations is one of the most important geotechnical studies widely studied in the light of the different technical and mechanical parameters of the ground. The calculations are based on the marginal balance method. The method of marginal analysis and others, despite the variety of calculation methods, the difference between the bearing capacity factors is very large, especially at large angles of friction. The use of the finite element method in the geotechnical field is very common for complex problems that require the determination of stresses and strains at each point of the ground. This thesis concerns the realization of a numerical study using the program Interaction of Finite Element Soil Structures (PLAXIS 3D) and with a variety of treatments, including layers of geogrids and layers of compacted soil, as well as the change by cementing the soil with stone poles in order to evaluate the effect of changing these treatments on the bearing capacity of the foundation under Concentrated Vertical Load on Clay Soil. Finally, we used the program (MATLAB) to analyze and compare the results extracted from the mentioned methods and visualize them visually using the graphs and tables available in the program Develop an artificial intelligence model to predict the bearing capacity of soils reinforced by geogrids (case of square feet)." "يعد حساب قدرة التحمل للاساسات من اهم الدراسات الجيوتقنية التي تدرس على نطاق واسع في ضوء مختلف من المعايير الهندسية والميكانيكية للتربة .وتستند الحسابات على طريقة التوازن الحدي . وطريقة التحليل الحدي وغيرها ،على الرغم من التنوع في طرق الحساب الا ان الفرق بين عوامل قدرة التحمل واسع جدا ، خاصة عند زوايا الاحتكاك الكبيرة . استخدام طريقة العناصر المنتهية في مجال الجيوتقنية امر شائع جدا من اجل المسائل المعقدة والتي تتطلب تعيين الاجهادات والتشوهات في كل من نقاط تربة . تهتم هذه الاطروحة باجراء دراسة عددية باستخدام برنامج تفاعل هياكل العناصر المحدودة للتربة (PLAXIS 3D )وبتنوع العديد من المعاملات بما في ذلك طبقات من geogrills وطبقات من التربة المرصوصة وكذلك التغيير بتدعيم التربة باعمدة حجرية من اجل تقييم تاثير التغييير في هاته المعاملات على قدرة تحمل الاساس تحت حمولة راسية مركزة على تربة طينية قمنا اخيرا باستخدام برنامج (MATLAB) لتحليل ومقارنة النتائج المستخرجة من الطرق المذكورة وتصورها بصريًا باستخدام الرسوم البيانية والمخططات المتوفرة في البرنامج . وصول لتطوير نموذج ذكاء اصطناعي للتنبؤ بقدرة تحمل التربة المعززة بواسطة geogrids (حالة قدم مربع)"
مذكرات ماستر تخصص هندسة مدنية des thèses génie civil
Keywords: "Numerical modeling ,shallow foundation, bearing capacity, the soil, PLAXIS 3D ,MATLAB, artificial intelligence"; "بلاكسيس ثلاثي الأبعاد , قدرة تحمل , التربة, النمذجة العددية , أساس سطحي MATLAB . ذكاء اصطناعي"